Local Economics Empowerment and Sharia Microfinance in Rural Community Perception - Umiyati Umiyati (Shirkah: Journal of Economics and Business, 2017)
This paper proposes to analyze and gain empirical evidences of the rural community perception on sharia micro finance institution to empower local economics at Margoyoso-Pati District Central Java, Indonesia. The data were gathered with survey method and questionnaire. The analysis technique in use is multiple linear regressions. The findings of the paper shows significant evidences on constructed research hypothesis, namely the products of Sharia Micro Finance Institution and the its services affecting the rural community perception on the sharia one, whereas on parametrically (t statistic test) and simultaneous (F statistic test). It shows better rural community knowledge and understanding on offered products from the Sharia Micro Finance Institution and their services quality; the two variables will simultaneously and parametrically affect rural community perception on Sharia Micro Finance Institution to empower local economics.Keywords: economic empowerment, service quality, rural community perception, sharia micro finance